ANALYSIS OF CUSTOMER PERCEIVED VALUE and its IMPACT on CUSTOMER BRAND PREFERENCE and FUTURE PURCHASE INTENTION - Muzakir Muzakir; Damrus Damrus (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2018)
Abstract. This research aims to analyse the impact of customer perceived value on customer brand preference and future purchase intention on customer of 7-eleven convenience store in Indonesia. The population are all previous customer of 7-eleven in Indonesia. Sample are acquired by using non-probability sampling method. Questionnaire are used to draw the samples out of population. Multiple regression analysis is used to analyse the relationship among variables. The finding shows that customer perceived value and customer brand preference has positive significant value toward future purchase intention. Customer brand preference has bigger impact toward future purchase intention than customer perceived value. The finding also reveals that 7-eleven still maintain positive perceived value and brand preference however, it is advised that the company should reconsider its brand positioning. Key words: Customer Behaviour, Customer brand preference, Customer  perceived value, Future purchase intention